ANALISIS PERBANDINGAN VARIABEL KINERJA KEUANGAN PERUSAHAAN PT SELAMAT SEMPURNA TBK - Sumarlan Sumarlan; Trilastiti Suryaningtyas; Sri Hermuningsih (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study was conducted to analyze the company PT. Selamat Sempurna Tbk. by analyzing the liquidity ratio (current ratio and quick ratio), activity ratio (receivables turnover ratio, inventory turnover ratio, fixed asset turnover ratio and total turnover ratio (assets/assets) and debt ratio by taking a sample of PT. Selamat Sempurna Tbk using the financial report for the 2022-2023 financial year. The research method used is a qualitative descriptive method, namely by collecting, processing, analyzing and presenting data descriptively with a sample of the financial report of PT. Selamat Sempurna Tbk for the 2022-2023 financial year. The results of the study obtained from the assessment of the financial performance of PT. Selamat Sempurna Tbk show significant revenue growth and an increase in net profit reflecting an effective business strategy and good management. The company has succeeded in adapting to industry challenges and remains competitive in the market. Keywords: Liquidity Ratio, Activity Ratio, Debt Ratio, Profitability